GENERAL DATA PROTECTION ACT (LGPD) AND ITS IMPLICATIONS IN BIOMETRIC MONITORING (Revista Paradigma, 2025)
In a society where information has become a financial asset, personal data is often treated without due care and even irresponsibly shared by the most diverse interests, exposing the person, their privacy, honor, security and even their heritage to free curiosity, not to mention the pecuniary frauds of unimaginable proportions, which can also tarnish many other attributes of the personality, such as reputation and image, and these conducts are often perpetrated with total disregard for constitutional and legal provisions that protect privacy and private life. In this context, aiming at a cut in the multiplicity of situations in which personal data can be collected, as well as the possibility of not ensuring the necessary and adequate conservation and use, this article proposes to think about the personal information collected and stored through biometric monitoring for future use, combining it with the security that the General Data Protection Act (Law 13.709/2018) LGPD added for a more responsible conduct of the administrators of this information in the promotion of fundamental rights. In this context, through bibliographic research and a qualitative deductive method, the relevance of the LGPD was proved due to the deficiency of the legislative system then in force to protect the citizen from the risks of access to an increasingly digitized world of information that has more vital information about individuals.
Keywords: Biometrics. Fundamental rights. Privacy. Personal data